Membrana amniótica descelularizada como substituto dérmico no processo de regeneração de queimaduras - Doi, Songila Maria da Silva Rocha (2015)
3rd degree of burns are one of the greatest injury that a human being can be submitted and generally are the most frequent injuries in the world population, in the case of a major public health problem. Thinking this problem, it has been observed that the use of amniotic membrane (AM) may be the best treatment these patients can receive. It acts on behalf of epithelialization, facilitates migration and adhesion of basal epithelial cells, stromal matrix has protease inhibitors which prevent apoptosis and restores epithelial, antibacterial phenotype of the chorion and amnion, and protect the wound and act on reducing pain. The decellularization, it is the withdrawal of all cells and core AM used as a way to avoid any kind of histoincompatibility. This study aimed to evaluate the efficacy of the decellularized amniotic membrane (DAM) in the treatment of third degree burns in humans, tested in Wistar rats. It is a descriptive research which investigates mainly the specification and the arrangement of data on the results obtained from a regenerative process burns using DAM. The sample consisted of consisted of 20 Wistar adult male rats, divided into 2 groups (n = 10): control group (CG) - without MA, and group transplanted - with AM (TDAM). The two groups were submitted to a standard process of thermal burn, two samples being removed tissue for analysis on day 14 and day 30. Samples were analyzed with the use of pathological techniques which were mounted on slides DNA fragments stained with solution hematoxylin eosin (HE) for histomorphometric analysis, the slides were stained with picrosirius red under polarized light for verification of decellularization and quantifying collagen type I, II and III. Images were quantified using Image Pro Plus ®, version 5.0 for Windows. Statistical data were analyzed using the computer program SPSS v.21.0. There was a significant increase in type III collagen quantification on the 14th day in TDAM group compared to CG, type II collagen in the 14th and 30th day compared to the CG and type I collagen in the 14th and 30th day, showing that the use of MA were effective in TDAM group. It was concluded that the DAM, applied topically, has shown efficacy in the healing process in 3rd degree burns. It was expected that it would promote accelerated wound healing but which was observed at the end of work that MAD is not only promoted as the healing was more efficient the regeneration process of the damaged tissues.